1996
DOI: 10.1177/095632029600700302
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Potent and Prolonged Inhibition of Herpes Simplex Virus Replication in Human Cell Lines by Penciclovir

Abstract: SummaryThe replication of herpes simplex virus type 1 (HSV-1) or HSV-2 in MRC-5 cells infected at 0.01 pfu ceni and treated continuously for 72 h, was inhibited more efficiently by penciclovir than aciclovir (p =0.0001).However, multiple cycles of replication were required in order to distinguish the compounds. Virus from cultures treated for 72 h with either compound, at 3 or 10 /1g mr", was resistant to penciclovir and aciclovir (50% effective concentrations> 10 /1g mr"), but infectivity titres of supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…More recent experiments in murine models for systemic HSV infection provided further weight for this hypothesis (Boyd et al, 1988;Sutton & Boyd, 1993;Ashton et al, 1994). Several workers have reported an effect of PCV in tissue culture that appeared to persist for up to several days after removal of the drug (Weinberg et al, 1992;Bacon & Schinazi, 1993;Standring-Cox et al, 1994;Bacon & Howard, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…More recent experiments in murine models for systemic HSV infection provided further weight for this hypothesis (Boyd et al, 1988;Sutton & Boyd, 1993;Ashton et al, 1994). Several workers have reported an effect of PCV in tissue culture that appeared to persist for up to several days after removal of the drug (Weinberg et al, 1992;Bacon & Schinazi, 1993;Standring-Cox et al, 1994;Bacon & Howard, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…, Shun-ichi NAGATA 2) , Takashi YAMANAKA 1) , Manabu NEMOTO 1) , Takashi KONDO 1) , Masahiko KUROSAWA 2) and Tomio MATSUMURA Equine herpesvirus type 1 (EHV-1) is a major causative agent of respiratory disease in horses and can also lead to abortion and neurological disease [1]. In particular, the recent increase in neurological EHV-1 outbreaks among horses in the U.S.A., the U.K. and Europe is of major concern to the horse industry worldwide, since affected animals often have a poor prognosis [7,8,[17][18][19][20].…”
mentioning
confidence: 99%
“…However, it has been reported that the intracellular half-lives of penciclovir triphosphate are much longer than those of acyclovir triphosphate in human cells infected with herpes simplex virus type 1 (HSV-1), type 2 (HSV-2), or varicella-zoster virus (VZV) (10 hr vs. 0.7 hr, 20 hr vs. 1 hr, and 9.1 hr vs. 0.8 hr, respectively) [3,10,33]. Additionally, in both tissue culture [2] and animal infection [6,28], penciclovir has a more sustained antiviral effect than acyclovir against HSV-1 and -2, a finding that may be correlated with the difference in the stability of the 2 compounds in infected cells. If penciclovir triphosphate is more stable than acyclovir triphosphate in EHV-1-infected cells as well, then it might be possible to obtain therapeutic efficacy of famciclovir via a dosage regimen using lower dose than that required for valacyclovir therapy.…”
mentioning
confidence: 99%